2013
DOI: 10.1002/humu.22440
|View full text |Cite
|
Sign up to set email alerts
|

An Overview and Online Registry of Microvillus Inclusion Disease Patients and theirMYO5BMutations

Abstract: Microvillus inclusion disease (MVID) is one of the most severe congenital intestinal disorders and is characterized by neonatal secretory diarrhea and the inability to absorb nutrients from the intestinal lumen. MVID is associated with patient-, family-, and ancestry-unique mutations in the MYO5B gene, encoding the actin-based motor protein myosin Vb. Here, we review the MYO5B gene and all currently known MYO5B mutations and for the first time methodologically categorize these with regard to functional protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
70
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 87 publications
3
70
0
Order By: Relevance
“…13,14), recently identified as aberrant Rab11-Rab8-positive recycling compartments (17). Genetic analysis revealed that mutations in the MYOB5 or STX3 genes are causative for MVID (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…13,14), recently identified as aberrant Rab11-Rab8-positive recycling compartments (17). Genetic analysis revealed that mutations in the MYOB5 or STX3 genes are causative for MVID (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted the predominant splice variant of MYO5B in enterocytes lacks exon D (17). Mutations that disrupt the function of the motor, lever arm, calmodulin binding, or RAB binding or induce premature termination before the tail domain can lead to MVID (1,4,6,9).…”
Section: Introductionmentioning
confidence: 99%
“…No studies until now have identified conclusively the origin or nature of these structures (22,23). The accumulation of PAS-positive "granules" also occurs at higher frequency in samples from patients with MVID than in the enterocytes of normal duodenum (9). MVID is uniformly fatal and no current pharmacotherapy exists, but it can be treated with total parenteral nutrition or an intestinal transplant (24).…”
Section: Introductionmentioning
confidence: 99%
“…An international patient registry reports 41 unique myosin Vb mutations thought to be associated with MVID (van der Velde et al, 2013). Myosin Vb is an actin based molecular motor.…”
Section: Introductionmentioning
confidence: 99%